Pengaruh Temperatur Karbonisasi Terhadap Karakteristik Briket Berbasis Arang Sekam Padi Dan Tempurung Kelapa - Nur Afrianah; Rustan Ruslan; Heri Rahmat Suryadi; Irmawati Amir; Al Irsyad; Jasruddin; Nurhayati (JFT : Jurnal Fisika dan Terapannya, 2022)
The effects of carbonized temperature on the briket-based properties of rice husks and coconut shells. This study aims to determine the effects of carbonization on brique-based, rice husk and coconut shell which include water content, ash content, volatile matter content, and calorific value. The research method used in this study is purely experimental within a process of carbonization of rice husk divested by free variables at temperatures of 300°C, 400°C, and 500°C for 30 minutes and carbonized coconut shells with a constant variable temperature of 500°C for 2 hours. Measures of a rice chaff and coconut shell of 200 mesh. Making briquettes with fixed variables, namely the composition of rice husk charcoal: coconut shell charcoal = 1: 3 (5 g:15 g) and printed using a pressure of 99.91 kPa. Then do the testing of water content, ash content, volatile matter and heating value. Test results on each type of briquettes with variations in the temperature of 300°C rice husk carbonization and 500°C coconut shell, 400oC rice husk carbonization temperature and 500°C coconut shell and 500°C rice husk carbonization temperature and 500°C coconut shell temperature were respectively obtained for 0.78% water content , 0.56% and 0.41%, ash content of 42.40%, 35.50% and 32.70%, volatile matter of 26.19%, 24.92% and 24.38%, and calorific value amounted to 3381.70 cal/g, 4261.50 cal/g, and 4621.50 cal/g.